DAMPAK DISKRIMINASI GENDER TERHADAP TINGKAT PUTUS SEKOLAH PEREMPUAN DAN AKSES TERHADAP PELUANG KERJA DI KOTA MAKASSAR - Maemunah; Mukramin, Sam'un; Ismail, Lukman; Nursida, Andi (SOSIORELIGIUS, 2025)
This study examines the impact of gender discrimination on female dropout rates and their access to employment opportunities in Makassar City, Indonesia. This study used a qualitative approach with in-depth interviews with 30 women aged 15 to 30 who dropped out of school or had difficulty accessing employment. The results showed that female dropout rates ranged from 15-20%, which was caused by social norms that prioritize women's traditional roles, lack of family support, and economic constraints. Only 25% of women from low-income families continued their education to college. Gender discrimination also hinders women from accessing formal employment, with the majority trapped in the informal sector with low incomes. This study highlights the need for effective policy interventions to improve education and employment opportunities for women. These findings provide insights for policy makers to create an environment that supports gender equality in education and employment, while changing public perceptions about women's roles. This study is expected to be a reference for efforts to improve women's welfare in Makassar.